An Analysis of Linguistic Intelligence in Gifted and Talented Children of Muslim Schools - Dwijayanti, Regina; Syafril, Syafrimen (International Journal of Islamic Studies Higher Education, 2024)
The lack of understanding from educators and parents of linguistic intelligence in gifted and talented children in Muslim schools can hinder children's linguistic development. For this reason, this research aims to analyze in depth the stages of linguistic intelligence in gifted and talented children, who show extraordinary abilities in speaking, listening, reading and writing. So that this research will produce complex research to find out the stages of linguistic intelligence in gifted and talented children for early childhood. This research uses the Systematic Literature Review (SLR) method with Nvivo 12 software. 35 relevant articles were analyzed through thematic coding to identify data patterns. As a result, five stages of linguistic intelligence were found: i) pre-linguistic (0-2 years), ii) vocabulary acquisition (2-3 years), iii) early simple sentences (3-4 years), iv) complex sentences (4-5 years), and v) narratives and stories. This research confirms the importance of creating an age-appropriate educational environment and appropriate stimulation to accelerate the linguistic development of gifted children.